Location selection of a manufacturing unit using BWM and ELECTRE III - Makarevic, Masa; Stavrou, Sofia (Journal of Supply Chain Management Science, 2022)
One of the most essential factors in a company's overall supply chain management success is the location of its manufacturing facilities. Due to the emerging energy crisis, the demand for insulation materials is rising, which increases the competition for insulation material companies. To stay competitive, the companies might consider expanding to different locations. This decision entails the consideration of various factors and alternatives, which could be formulated as a multi-criteria decision-making (MCDM) problem. This paper contributes to the problem of location selection in the chemical industry, by implementing two MCDM methods, Best-Worst Method (BWM) and ELECTRE III, in a real-world case company. Based on a thorough literature study and data from interviews with the decision-makers, seven criteria and nine countries as alternatives were chosen. The BWM was used to elicit the weights of all the criteria from a group of decision-makers. Then, ELECTREE III was used to generate a ranking of the alternative countries. Based on the results, the main recommendation to the case company was to choose France as the most appropriate location for the new manufacturing unit. The findings of this research have insights for other companies in the chemical industry deciding on new locations for their manufacturing.